2016
DOI: 10.1136/bmjopen-2015-010159
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-height ratio as an indicator of ‘early health risk’: simpler and more predictive than using a ‘matrix’ based on BMI and waist circumference

Abstract: ObjectivesThere is now good evidence that central obesity carries more health risks compared with total obesity assessed by body mass index (BMI). It has therefore been suggested that waist circumference (WC), a proxy for central obesity, should be included with BMI in a ‘matrix’ to categorise health risk. We wanted to compare how the adult UK population is classified using such a ‘matrix’ with that using another proxy for central obesity, waist-to-height ratio (WHtR), using a boundary value of 0.5. Further, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
346
2
42

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(415 citation statements)
references
References 32 publications
25
346
2
42
Order By: Relevance
“…Sri Lanka'da Güney Asya kö-kenli etnik bir grupla yürütülen çalışmada da bel/boy oranının BKİ, bel çevresi ve bel/kalça oranına kıyasla tip 2 diyabet ve metabolik sendrom riskinin belirlenmesinde etkili olduğu belirlenmiş-tir (Jayawardana, Ranasinghe, Sheriff, Matthews, & Katulanda, 2013). Özetle, bel/boy oranının abdominal obeziteyle ilgili hastalık risklerinin belirlenmesinde BKİ ve bel çevresine göre daha etkili olabileceği bildirilmektedir (Ashwell & Gibson, 2016). Bu bağlamda bel/boy oranı, BKİ değerleri normal olup insülin direnci ve hiperlipidemi belirtilerinin gözlendiği metabolik obezite riskinin belirlenmesinde de etkili olabilmektedir.…”
Section: Bulgular Ve Tartışmaunclassified
“…Sri Lanka'da Güney Asya kö-kenli etnik bir grupla yürütülen çalışmada da bel/boy oranının BKİ, bel çevresi ve bel/kalça oranına kıyasla tip 2 diyabet ve metabolik sendrom riskinin belirlenmesinde etkili olduğu belirlenmiş-tir (Jayawardana, Ranasinghe, Sheriff, Matthews, & Katulanda, 2013). Özetle, bel/boy oranının abdominal obeziteyle ilgili hastalık risklerinin belirlenmesinde BKİ ve bel çevresine göre daha etkili olabileceği bildirilmektedir (Ashwell & Gibson, 2016). Bu bağlamda bel/boy oranı, BKİ değerleri normal olup insülin direnci ve hiperlipidemi belirtilerinin gözlendiği metabolik obezite riskinin belirlenmesinde de etkili olabilmektedir.…”
Section: Bulgular Ve Tartışmaunclassified
“…The importance of examining AO using low-cost anthropometric indices may contribute to identify cardiometabolic risk factors from adolescence through adulthood [34]. Thereby, simple anthropometric measures of AO, such as waist circumference (considering ethnicity, sex, and age) [37,38], waist to hip ratio, and waist to height ratio (independent of age, gender or race/ethnicity), could be considered as predictors of AO [11,39]. In this sense, a number of studies have shown that surrogate markers of AO are independent risk factors for type 2 diabetes mellitus, dyslipidemia, hypertension, and coronary artery disease [28,40].…”
Section: Abdominal Obesity and Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…Among the common risk factors for CVDs, body mass index (BMI) is often used to assess a population’s risk because it is easily measured, inexpensive and associated with all-cause mortality [3]. Despite the controversy regarding the use of BMI [47] to predict disease, BMI remains the most commonly used marker of whole body obesity. By 2014, it was estimated that approximately a billion adults were overweight and that 600 million were obese worldwide [8].…”
Section: Introductionmentioning
confidence: 99%